Analisis Yuridis Terhadap Penetapan Ahli Waris Kalalah (Studi Putusan Penetapan Pengadilan Agama Nomor 455/Pdt.P/2021/PA.Mks) - A. Saule, Riski Safitri; Hasibuddin, M.; Sumardin, Andi (Media Hukum Indonesia (MHI), 2025)
This study examines heirs, specifically in the case of "kalalah" (inheritance) in the ruling of the Religious Court under Case Number 455/Pdt.P/2021/PA.Mks. The problem concerns the resolution of the kalalah inheritance case at the Makassar Class 1A Religious Court and the judge's considerations in deciding the kalalah case in decision 455/Pdt.P/2021/PA.Mks. This study employed qualitative research with a normative descriptive method. Data sources were obtained through interviews with informants from clerks or judges at the Makassar Class 1A Religious Court. Data also included religious court decision documents, references in the form of journals, books, laws and regulations, and articles related to this research. The results of this study indicate that the resolution of kalalah inheritance cases follows the same stages as other inheritance cases. However, the only difference lies in the root cause of the problem; in resolving the issue, judges at the Makassar Religious Court refer to the Islamic inheritance legal system, namely the Compilation of Islamic Law (KHI) and Islamic Law. Apart from that, the judge's considerations in determining case number 455/Pdt.P/2021/PA.Mks were based on the provisions of Allah Q.s An-Nisa verses 12 and 176 as well as KHI article 171 letter (c) and article 174 paragraph (1) as well as the hadith of the Prophet SAW.